2014
DOI: 10.1186/1756-3305-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of beta carbonic anhydrase sequences from protozoans and metazoans

Abstract: BackgroundDespite the high prevalence of parasitic infections, and their impact on global health and economy, the number of drugs available to treat them is extremely limited. As a result, the potential consequences of large-scale resistance to any existing drugs are a major concern. A number of recent investigations have focused on the effects of potential chemical inhibitors on bacterial and fungal carbonic anhydrases. Among the five classes of carbonic anhydrases (alpha, beta, gamma, delta and zeta), beta c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 72 publications
1
25
0
Order By: Relevance
“…One of them was β‐CA protein sequence from T. spiralis (UniProt ID: E5SH53). Our previous results also revealed that β‐CA proteins show high similarity among various Drosophila species and other species of dipteran flies (Zolfaghari Emameh et al ., ). This led us to hypothesize that the high similarity is extensible to other species of one defined genus, such as Trichinella spp.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…One of them was β‐CA protein sequence from T. spiralis (UniProt ID: E5SH53). Our previous results also revealed that β‐CA proteins show high similarity among various Drosophila species and other species of dipteran flies (Zolfaghari Emameh et al ., ). This led us to hypothesize that the high similarity is extensible to other species of one defined genus, such as Trichinella spp.…”
Section: Discussionmentioning
confidence: 97%
“…Many protozoan, arthropod, and nematode species (invertebrate metazoans) contain β-CA gene and protein sequences in their genomes and proteomes respectively. BLAST homology analysis of predefined β-CA protein sequences from D. melanogaster (Uniprot ID: Q9VHJ5) and C. elegans (Uniprot ID: Q22460) resulted in identification of more than 75 β-CA protein sequences from protozoans and invertebrate metazoans (Zolfaghari Emameh et al, 2014). One of them was β-CA protein sequence from T. spiralis (UniProt ID: E5SH53).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations